Association between mild renal dysfunction and insulin resistance or metabolic syndrome in a random nondiabetic population sample - Onat, Altan; Hergenc, Gulay; Uyarel, Huseyin; Ozhan, Hakan; Esen, A. Metin; Karabulut, Ahmet; Albayrak, Sinan; Can, Gunay; Keles, Ibrahim (KARGER, 2007)
Aims: The association of mild renal dysfunction (estimated glomerular filtration rate [eGFR] 60-89.9 ml/min/1.73 m(2)) with insulin resistance (IR) or metabolic syndrome (MS) needs be investigated in a population in which MS prevails. Methods: After excluding subjects with diabetes mellitus, 1,678 subjects from a representative cohort (median age 52 years) were studied cross sectionally. eGFR was based on serum creatinine concentrations using the quadratic GFR equation and categorized by 90 and 60 ml/min/1.73 m(2) as limits. MS was identified using the modified criteria of the Adult Treatment Panel-III. Results: In men, whereas MS was not significantly associated with a reduced eGFR category when controlled for homeostatic model assessment (HOMA), HOMA adjusted for MS or for its components was significantly associated with the likelihood of a reduced eGFR. This likelihood was increased by 14% with a doubling of HOMA in men. Age was the dominant correlate of reduced eGFR in women, whereby an association with HOMA was not significant. Conclusion: Mildly impaired kidney function is common in nondiabetic adults among whom MS prevails, and in men it is mainly associated with IR but not with central obesity and MS-related dyslipidemia. The quadratic GFR equation enables an acceptable estimation of GFR in a general population. Copyright (c) 2007 S. Karger AG, Basel.
Keywords: dyslipidemia; glomerular filtration rate; kidney dysfunction; insulin resistance; metabolic syndrome; GLOMERULAR-FILTRATION-RATE; CHRONIC KIDNEY-DISEASE; CARDIOVASCULAR MORTALITY; ATHEROSCLEROSIS RISK; SERUM CREATININE; PLASMA-LIPIDS; HYPERINSULINEMIA; CHOLESTEROL; Physiology; Urology & Nephrology; Cardiovascular System & Cardiology